The Relationship between Learning Agility and Work Engagement on Organizational Commitment among the Strawberry Generation - Jocelyn Patricia; Marchelina Febe Sumbaga (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
In the industrial world, organizational success in the VUCA era hinges on employee commitment, yet the